Ferromagnetic shape memory alloys : selected peer reviewed papers from the International Conference on Ferromagnetic Shape Memory Alloys - Mañosa, Lluís (Advanced materials research ;, 2008)
Multiferroic shape-memory alloys that exhibit both ferroelastic and ferromagnetic properties have recently attracted much attention. They belong to the family of so-called "smart materials" and are future-generation materials that are likely to be useful in cutting-edge technologies. Apart from the theoretical challenge of understanding their fascinating properties, the quest to harness them for practical use is also attracting many scientists and engineers from all over the world. This compilation comprises peer-reviewed papers, categorized into: I. Sample Preparation, II Thermal Treatments and Phase Stability, III. Magnetic and Structural characterization, IV. Microscopic studies of Magnetic Shape Memory Alloys, V. Effects of External Fields, VI. Coupled Effects: Magnetoresistance and Magnetocaloric effects. The volume thus provides a comprehensive introduction to this exciting new field